Cold War Civil Defence in Western Europe
XV, 250 p. 9 illus., 6 illus. in color.
Keywords: “With its geographical focus on Western Europe and its application of the concept of sociotechnical imaginaries from science and technology studies, Cold War Civil Defence in Western Europe breaks new ground.” – Christoph Laucht, Swansea University, UK "Too often, Cold War civil defence history has been limited to the two superpowers in the 1950s and early 1960s. This compelling collection demonstrates a great diversity of civil defence plans, periodizations, material interventions, and public responses across a number of NATO and neutral countries." – David Monteyne, University of Calgary, Canada This open access edited collection brings together established and new perspectives on Cold War civil defence in Western Europe within a common analytical framework that also facilitates comparative and transnational dimensions. The current interest in creating disaster-resilient societies demands new histories of civil defence. Historical contextualization is essential in order to understand what is at stake in preparing, devising, and implementing forms of preparedness, protection, and security that are specifically targeted at societies and citizens. Applying the concept of sociotechnical imaginaries to civil defence history, the chapters of this volume cover a range of new themes, from technology and materiality to media, memory, and everyday experience. The book underlines the social embeddedness of civil defence by detailing how it both prompted new forms of social interaction and reflected norms and visions of the ‘good society’ in an age where nuclear technology seemed to hold the key to both doom and salvation.